2003
DOI: 10.1590/s0041-87812003000200010
|View full text |Cite
|
Sign up to set email alerts
|

Parosteal osteosarcoma with myocardial metastasis 13 years after follow-up

Abstract: The review leads to the conclusion that the occurrence of metastasis from parosteal osteosarcoma can occur in up to 38% of the cases, in spite of its relatively low aggressiveness. However, myocardial metastasis of a parosteal osteosarcoma is an event that was not found in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…With the evolution of the materials and surgical techniques, arthroscopy has become more of a surgical method than a diagnostic tool, and magnetic resonance is fast becoming the favorite diagnostic method for many of surgeons [52][53][54] . The results of the present study demonstrate that knee meniscal and cruciate ligament lesions can be accurately diagnosed by magnetic resonance and support the findings of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…With the evolution of the materials and surgical techniques, arthroscopy has become more of a surgical method than a diagnostic tool, and magnetic resonance is fast becoming the favorite diagnostic method for many of surgeons [52][53][54] . The results of the present study demonstrate that knee meniscal and cruciate ligament lesions can be accurately diagnosed by magnetic resonance and support the findings of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another point is that; case series demonstrate an average of 3.7 years before the diagnosis of cardiac metastasis, which was 7 years in our case [6]. Santos-Machado et al reported a case of parosteal osteosarcoma with myocardial metastasis after 13 years of follow-up [11]. As a result, radiological screening should be performed during a long follow-up phase especially in patients with multiple metastases.…”
Section: Discussionmentioning
confidence: 71%
“…Patients with incomplete surgery can have multiple recurrences, so multiple surgeries are not uncommon. [22][23][24] The longest recorded recurrence was 21 years after the initial operation. [25] Therefore, for low-grade malignant tumors of PO, the follow-up time should be long to facilitate close observation.…”
Section: Discussionmentioning
confidence: 99%